(3efgLjI GdHMK aj GdYdhe GdGLJeGYjIs - (3GSeGYjd(B, (3TYHGfjs ((3GdLRGFQ(B:s [(3O(B.(3f(B],s, 2005)
(3CfhGM GdHMhK GdYdejI, eQMdI GdJacjQ aj GdehVhY, ebOeI GdHMK, cjajI JbOje eTQhY GdHMK (B((3GdGTcGdjI(B)(3, efGgL GdHMK, cJGHI GdghGeT hGdJhKjb, WQjbI GNQi ddJhKjb hGdJgejT, WQb cJGHI eUGOQ GdLOGhd hGdCTcGd, cdeI GNjQI Yf GdJgejT, cJGHI GdeQGLY, GdUhQI GdfgGFjI ddHMK(B/ (3GdefGbTIs
(3HHdjhZQGajG(B: (3U(B.109-112 (3edGMb U(B.106s
Keywords: (3GdHMhKs; (3GdYdhe GdGLJeGYjIs; (3WQb GdHMKs